Pengolahan Sampah Organik dengan Teknologi Composter Bag di Kota Yogyakarta - Kurniantoro, Indra; Muzzaky, Moch Najwan; Erawati, Erawati; Farikah, Irma Khoiriathul; Pertiwi, Kharisma Mutiara; Kusmayadi, Ghaisani Khayyira Putri; Khaerunnisa, Akmalya; Tulloh, Putra Nur Hidayat; Abimanyu, Anggito Radya; Widyatmaka, Muhammad Davin; Setiawan, Agus Nugroho (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The problem of organic waste in RW 06, Pandeyan Village, Umbulharjo District, Yogyakarta City, is increasingly pressing due to limited land and population density, which hinder the implementation of conventional management methods such as biopores. In response, community service was carried out to provide alternative solutions with the composter bag method, which is more practical and follows local environmental conditions. This program was implemented through stages of socialization, direct practice training, and assistance in implementing composter bags in the community environment. The results of the activities showed an increase in community participation in managing organic waste independently, thus contributing to the reduction of organic waste and its use as compost fertilizer that can be used for small-scale agriculture. The evaluation results showed an increase in participants' understanding regarding waste management and the process of processing it into organic fertilizer, with an average increase of 11.63%. In addition, there is an increase in knowledge from before to after the programs. The success of this program proves that an educational approach based on practice can increase community awareness and skills in managing organic waste more efficiently, sustainably, and environmentally friendly